Modifikasi Kulit Telur Puyuh Dan Serbuk Besi Menjadi Katalis CaO/Serbuk Besi Untuk Reaksi Transesterifikasi Minyak Sawit Off Grade Produksi Biodiesel - Vandhe Melsa Sembiring; Zuchra Helwani; Rozanna Sri Irianty (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
Biodiesel can be synthesized from palm oil off grade using a CaO / iron powder catalyst in the transesterification stage. This study aims to produce biodiesel from low-quality raw materials and determine the effect of the process by looking at the effect of process conditions such as dehydration temperature and dehydration temperature on biodiesel yield. The process of making biodiesel is carried out by esterification and transesterification reactions. The catalyst with the highest catalytic activity was obtained at a dehydration temperature of 600°C and dehydration time for 3 hours with the condition of the transesterification reaction at 10:1 molar ratio of methanol/oil, catalyst concentration of 1% -b oil, reaction temperature of 70° C for 2 hours with yield biodiesel reached 90%. Keywords: biodiesel, CaO, off grade palm oil, iron powder, transesterification.